Analisis Penyebab Cacat Cekung Profil Aluminium Bangladesh Window Dengan Metode FMEA - Murwan Widyantoro (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2021)
Quality control is a necessary requirement to keep the business running. By maintaining product quality there will be continuous business. PT.XYZ is a company engaged in manufacturing aluminum products. One of the products produced is the Bangladesh aluminum window profile. Currently, the production of Bangladesh window aluminum profiles is still often defective. This study aims to determine the root cause of the failure that occurred in the Bangladesh window aluminum profile product. The number of defects that occur is on the concave surface type with the results of the analysis using fish bone and the number of values of Severity 10, Occurance 10 and detection value 10. The results of FMEA calculations are 7 failures that occur, namely at the highest rank with a value of 120 by the state of the die draw surface. less evenly on the inside resulting in a concave-shaped aluminum profile.